Comparação da modulação condicionada da dor, somação temporal, limiar de dor por pressão, força muscular e cinemática angular em mulheres com e sem dor femoropatelar - Albuquerque, Tadeu Aldrovando Brihy de (2019)
Introduction: The etiology of patellofemoral pain (PFP) is multifactorial, and the treatment is multimodal, it is necessary to understand the various factors that can influence it. Many studies have already addressed biomechanical issues, but the evidence about factors related to pain sensitization is still considered moderate to limited. Objective: To compare the pressure pain threshold (PPT), temporal summation (TS), conditioned pain modulation (CPM), angular kinematics and muscle strength among women with PFP and asymptomatic, and to correlate the pain sensitization variables with the biomechanics in women with PFP. Method: Cross-sectional study with 26 women with PFP and 24 asymptomatic. The PPT was evaluated in points of the knee, tibialis anterior and elbow, for the TS and the CPM the mean value of the PPT was used, in the TS ten consecutive stimuli were performed and in the CPM the cold water was used as a conditioning stimulus. Was performed a strength assessment of the abductor, extensor and lateral hip rotator and knee extensor muscles with the manual dynamometer and the three-dimensional kinematics of the lateral step-down test taking into account the peak values, range of motion and Movement Deviation Profile (MDP). Results: Was found a lower value for the PPT of the knee and elbow and a higher value for the MDP for the PFP group. No correlation was found between the CPM and the PPT. Conclusion: The women evaluated in this study presented local and diffuse hyperalgesia, but without influence of the deficit in the downward modulation pain system, and showed no association between these variables and changes in movement.